2011
DOI: 10.1364/ao.50.002636
|View full text |Cite
|
Sign up to set email alerts
|

Wide-angle, nonmechanical beam steering with high throughput utilizing polarization gratings

Abstract: We introduce and demonstrate a ternary nonmechanical beam steering device based on polarization gratings (PGs). Our beam steering device employs multiple stages consisting of combinations of PGs and wave plates, which allows for a unique three-way (ternary) steering design. Ultrahigh efficiency (∼100%) and polarization sensitive diffraction of individual PGs allow wide steering angles (among three diffracted orders) with extremely high throughput. We report our successful demonstration of the three-stage beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 10 publications
0
60
0
Order By: Relevance
“…It is possible to configure PG steering designs that are based on either switchable [13], [14] or polymer [15] PGs. These designs all utilize at least one switchable LC variable retarder as the polarization selector/controller before each PG, which is needed to access the full FOR.…”
Section: Steering Design Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible to configure PG steering designs that are based on either switchable [13], [14] or polymer [15] PGs. These designs all utilize at least one switchable LC variable retarder as the polarization selector/controller before each PG, which is needed to access the full FOR.…”
Section: Steering Design Comparisonmentioning
confidence: 99%
“…With the three PGs prepared and three switchable LC WPs [14] optimized for 1550 nm wavelength (fabricated in-house), we assembled the 1D coarse steering module shown as the Fig. 4 with the order of PG3 (adjacent to the input), PG2, and PG1 consecutively.…”
Section: B 1d Coarse Steerer Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Escuti et al demonstrated defect-free, 100% efficient PGs as switchable diffractive elements. 5,6 Since these devices are not traditional gratings they exhibit very large acceptance angles while maintaining near 100% diffraction efficiency into a single order. This counterintuitive property is critical to our design.…”
Section: New Electro-optic Laser Scanners: Circumventing the Size Wementioning
confidence: 99%
“…The polarization state of the transmitted electric field is thus modulated periodically [1]. Because of its well-known interesting optical properties [2]- [5], a variety of applications have been proposed, including displays [6], polarimeters for measuring stokes parameters [7], [8] or Muller matrix [9], beam steering [10], [11], polarization conversion element [12] etc.…”
mentioning
confidence: 99%